Effectiveness Of Training And Coaching Strengthening Entrepreneurship In Improving Youth Business Competence (Descriptive study at the Bandung City Youth and Sports Office) - Eki Dudi Darmawan; Sutaryat Trisnamansyah; Adjat Sudrajat; Wiwik Dyah Aryani (International Journal of Educational Research & Social Sciences, 2021)
The era of the industrial revolution 4.0 is an opportunity in building the Indonesian economy with various facilities and conveniences provided by technological advances, as well as being a threat when it cannot be utilized properly, namely when human labor in the process of producing goods has begun to switch to digital, but not matched by the growth of new business units. This study focuses on training management and fostering youth entrepreneurship strengthening which is an effort to reduce unemployment by increasing business management competencies. The purpose of the research is to describe planning, organizing, implementing, evaluating training, coaching through mentoring the implementation of training results, implementation effectiveness, problems, and future improvement solutions. This study uses descriptive qualitative research methods in order to intensively and in depth describe the symptoms and phenomena studied, while data collection is carried out by observation, interviews, documentary studies, and literature studies. The findings in this study are that Bandung City Youth and Sport Department has carried out management of entrepreneurship strengthening training Which gave an impact on increasing the competence of training graduates. Yet entrepreneurship coaching through mentoring in the application of training results has not been carried out optimally, that in general training management and entrepreneurship strengthening development have not been effective in improving business management competencies among young man. This study recommends that in training for strengthening youth entrepreneurship, character and team building materials are given so that training participants from the beginning of training to entrepreneurship development remain in the same group of the business world, the industrial world (DUDI) as well as with BUMD/BUMN and banking to participate in fostering strengthening the management of youth businesses in the city of Bandung.